Origami-based Building Blocks for Modular Construction of Foldable Structures. Issue 1 (December 2017) - Mousanezhad, Davood; Kamrava, Soroush; Vaziri, Ashkan
Abstract Origami, widely known as the ancient Japanese art of paper folding, has recently inspired a new paradigm of design for mechanical metamaterials and deployable structural systems. However, lack of rationalized design guidelines and scalable manufacturing methods has hindered their applications. To address this limitation, we present analytical methods for designing origami-based closed-loop units with inherent foldability, and for predicting their folding response (e.g., folding force, bistability, and area and volume change by folding). These units can be employed as building blocks for application-driven design and modular construction of foldable structures with desired performance and manufacturing scalability.